2017
DOI: 10.1063/1.4990069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pseudo-gravitational acceleration on the dissolution rate of miscible drops

Abstract: The effect of pseudo-gravitational acceleration on the dissolution process of two phase miscible systems has been investigated at high acceleration values using a spinning drop tensiometer with three systems: 1-butanol/water, isobutyric acid/water, and triethylamine/water. We concluded that the dissolution process involves at least three different transport phenomena: diffusion, barodiffusion, and gravitational (buoyancy-driven) convection. The last two phenomena are significantly affected by the centrifugal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…By measuring the drop radius and using Vonnegut’s formula (see below), he inferred the effective (transient) interfacial tension between the fluids. Similar measurements were performed by J. Pojman and co-workers, who investigated the existence of an effective interfacial tension (EIT) between miscible fluids and discussed its importance, using (i) mixtures of Isobutyric acid and water close to their critical point and (ii) dodecyl acrylate drops in poly­(dodecyl acrylate). They concluded that capillary forces are at work at the boundary between these fluids and quantified the EIT, again using Vonnegut’s theory.…”
Section: Introductionmentioning
confidence: 59%
“…By measuring the drop radius and using Vonnegut’s formula (see below), he inferred the effective (transient) interfacial tension between the fluids. Similar measurements were performed by J. Pojman and co-workers, who investigated the existence of an effective interfacial tension (EIT) between miscible fluids and discussed its importance, using (i) mixtures of Isobutyric acid and water close to their critical point and (ii) dodecyl acrylate drops in poly­(dodecyl acrylate). They concluded that capillary forces are at work at the boundary between these fluids and quantified the EIT, again using Vonnegut’s theory.…”
Section: Introductionmentioning
confidence: 59%